Synthesis and characterizations of iron antimony oxide nanoparticles and its applications in electrochemical detection of carbendazim in apple juice and paddy water samples. (30th March 2022) - Yamuna, Annamalai; Chen, Tse-Wei; Chen, Shen-Ming
Highlights: The iron antimony oxide (FeSbO4 ) was synthesized by a simple sonochemical route. The FeSbO4 exhibits rutile type with the crystal system of tetragonal phase. FeSbO4 /GCE shows good electrocatalytic behavior for the detection of carbendazim. The FeSbO4 /GCE shows high selectivity with potential interfering compounds. It shows good recoveries in apple juice and paddy water samples. Abstract: This study reports a facile sonohydrolysis synthesis route to prepare the iron antimony oxide (FeSbO4 ) nanoparticles for the trace level electrochemical sensing of fungicide carbendazim (CRBZ). As prepared FeSbO4 nanoparticles show a nano-cubes-like morphology with uniform distributions that crystallized in the tetragonal phase. The diffraction studies reveal that the FeSbO4 nanoparticles have high crystallinity and high purity. Furthermore, the other structural properties and morphology are characterized by XRD, Raman, XPS, HRTEM, and FESEM analysis. The electrochemical characterizations of FeSbO4 modified GCE towards the detection of CRBZ are performed by cyclic voltammetry and chronoamperometry techniques. The FeSbO4 /GCE exhibits a linear range from 0.01 µmol L −1 to 64.3 µmol L −1, the sensitivity of 0.68 µA cm −2  µM −1, and the LOD of 5.4 nmol L −1 . Moreover, the FeSbO4 /GCE delivered high selectivity among the possibly interfering compounds. Also, our projected FeSbO4 /GCE electrode material shows good recoveries in apple juice and paddy water real samples.